Gene expression of inflammatory markers in adipose tissue between obese women with polycystic ovary and normal obese women - Alshammari, G.; Khan, Raheela; Brameld, John M.; Amer, Saad A.; Lomax, Michael A. (Verduci Editore, 2017)
OBJECTIVE: The pathogenesis of polycystic ovary syndrome (PCOS), a common endocrine disease and metabolic disturbance, is still unknown. The aim of the study was to investigate whether patients with PCOS display increased expression of inflammatory markers in adipose tissue. PATIENTS AND METHODS: Two groups of women were investigated, those diagnosed with PCOS (n = 8) and age and BMI-matched normal women (n = 12). Their age was between 20-45 years and all subjects were apparently healthy and did not take any medications. Adipose tissue levels of mRNA of inflammatory markers were determined by use of real-time PCR. RESULTS: There were no differences between obese patients and obese PCOS in levels of adipocytokines. CONCLUSIONS: There were no effects of PCOS on the expression of any of the adipocytokines genes measured in subcutaneous adipose tissue.